1987
DOI: 10.1210/endo-121-6-2256
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Negative Ultrashort Loop Feedback Mechanism Operating on the Luteinizing Hormone-Releasing Hormone Neuronal System

Abstract: The present studies were designed to determine whether an ultrashort loop feedback mechanism is involved in the regulation of LHRH secretion. Daily administration of a highly potent LHRH agonist (LHRH-AGO; [D-Ala6,Des-Gly10] LHRH ethylamide) immediately after orchidectomy (ORDX) significantly attenuated the rise of plasma LH from days 2 through 10 after ORDX. Concomitantly with the diminished LH rise after ORDX, a significant increase in LHRH content in the arcuate nucleus was observed in LHRH-AGO-treated rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
2

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 17 publications
2
56
2
Order By: Relevance
“…Key words; LHRH, Preoptic area, Feedback, LH, Ovariectomy, LHRH antagonist (Endocrine Journal 41: 559-563,1994) IT HAS BEEN reported that intraventricular injection of LHRH or LHRH agonist reduces the secretion of LHRH [1] and thus the secretion of LH is decreased in ovariectomized (OVX) rats [2, 3] and ewes [4], implying the existence of an ultra-short negative feedback mechanism for the control of LHRH secretion. In addition, in vitro studies have suggested that the neural structure that is involved in the mechanism is in the mediobasal hypothalamus including the median eminence [5,6].On the other hand, we have shown [7] that LHRH injected into the medial preoptic area (MPO) potentiates the surge of LH secretion in OVX estrogen-primed and proestrous rats, suggesting the existence of an ultra-short positive feedback mechanism in the MPO, instead of a negative one as reported by others. The discrepancies between our results and those of others might be due to differences of the influence of gonadal steroids or the site of injection.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…Key words; LHRH, Preoptic area, Feedback, LH, Ovariectomy, LHRH antagonist (Endocrine Journal 41: 559-563,1994) IT HAS BEEN reported that intraventricular injection of LHRH or LHRH agonist reduces the secretion of LHRH [1] and thus the secretion of LH is decreased in ovariectomized (OVX) rats [2, 3] and ewes [4], implying the existence of an ultra-short negative feedback mechanism for the control of LHRH secretion. In addition, in vitro studies have suggested that the neural structure that is involved in the mechanism is in the mediobasal hypothalamus including the median eminence [5,6].On the other hand, we have shown [7] that LHRH injected into the medial preoptic area (MPO) potentiates the surge of LH secretion in OVX estrogen-primed and proestrous rats, suggesting the existence of an ultra-short positive feedback mechanism in the MPO, instead of a negative one as reported by others. The discrepancies between our results and those of others might be due to differences of the influence of gonadal steroids or the site of injection.…”
supporting
confidence: 60%
“…Such differential effects of neuropeptides on LH secretion depending upon the site of microinjection in the brain were also found in the case of neurotensin; the injection of neurotensin into the MPO did not affect pulsatile LH secretion in OVX rats [13] but that into the third ventricle inhibited the LH secretion [14]. Intracerebroventricularly injected LHRH probably acts on hypothalamic areas other than the MPO; for example on the mediobasal hypothalamus [5,6], to inhibit its own secretion in OVX rats. Their results on the inhibition by intracerebroventricular LHRH injection are not inconsistent with our results showing no effect of LHRH injection into the MPO of OVX rats.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The activity of the GnRH pulse generator is influenced by several factors, including endothelin, N-methyl-D-aspartate, opiates, -aminobutyrate, and a-adrenergic input, as well as estrogens and androgens (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, GnRH has been proposed to exert an inhibitory action on its own secretion (17)(18)(19); however, the mechanism and circuitry of such an ultrashort loop feedback effect have not yet been defined. We now report that GnRH acts directly on immortalized GnRH neuronal cells to regulate its own secretion and that this autocrine action of the neuropeptide is associated with activation of calcium-mobilizing GnRH receptors expressed in its cells of origin.…”
mentioning
confidence: 99%